2021
DOI: 10.1186/s13287-021-02579-0
|View full text |Cite
|
Sign up to set email alerts
|

IL-1β-primed mesenchymal stromal cells exert enhanced therapeutic effects to alleviate Chronic Prostatitis/Chronic Pelvic Pain Syndrome through systemic immunity

Abstract: Background Chronic prostatitis/chronic pelvic pain syndrome (CP/CPPS) seriously affects patient health. Despite the elusiveness of innate therapeutic effects, mesenchymal stromal cells (MSCs) hold great promise for inflammation-related diseases. Recent evidence indicates that disease-specific inflammatory cytokines could enhance the therapeutic effects of MSCs. Methods By establishing a CP/CPPS mouse model and pretreating MSCs with the cytokine int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 105 publications
0
13
0
Order By: Relevance
“…Our previous study has shown that proper pretreatment enhanced the therapeutic effect of MSCs by regulating anti-inflammatory agents in the exosome [ 38 ]. On the other hand, MSCs exert a beneficial effect indirectly by modulating the function of neighboring immune cells [ 39 ]. Since the number of cells for injection is limited and the excess of MSCs may cause thrombosis, the engraftment rate of MSCs documented in injured areas is crucial.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study has shown that proper pretreatment enhanced the therapeutic effect of MSCs by regulating anti-inflammatory agents in the exosome [ 38 ]. On the other hand, MSCs exert a beneficial effect indirectly by modulating the function of neighboring immune cells [ 39 ]. Since the number of cells for injection is limited and the excess of MSCs may cause thrombosis, the engraftment rate of MSCs documented in injured areas is crucial.…”
Section: Discussionmentioning
confidence: 99%
“…Based on our CP/CPPS model and previously published studies, we found that inflammation in the mouse prostate was more severe, and we observed higher proportions of proinflammatory CD11b + Ly6C high monocytes/macrophages in the lung, spleen, and blood of the mice. This may indicate that the systemic immunity of the mice was changed by inflammation ( Liu et al, 2021 ). As we mentioned previously, CD11b + immune cells patrol the body and play a proinflammatory or anti-inflammatory role.…”
Section: Discussionmentioning
confidence: 99%
“…The most widely accepted animal model of CP/CPPS (NOD-EAP) was established as described in the Methods section; in this model, the tissue structure of the mouse prostate changed after the model was successfully established, and a large number of inflammatory cells infiltrated the prostate (Figure 2A). According to a previously published article (Liu et al, 2021), the inflammatory score was used to assess the inflammatory state, and it was found that the prostate tissue inflammatory score was significantly increased in the EAP group (p < 0.001), but the difference in body weight between the two groups was not statistically significant (p > 0.05) (Figure 2B). Von Frey pain behavior test filaments were used to measure the pain of the mice with EAP, and we found that the response frequency was significantly increased in mice with EAP (p = 0.002) (Figure 2C).…”
Section: Establishment Of the Chronic Prostatitis/ Chronic Pelvic Pai...mentioning
confidence: 99%
See 1 more Smart Citation
“…The aetiology and pathogenesis of CP/CPPS is still perplexing, and in recent years, infection, defective function of urothelial, abnormal gut microbiota, psychosocial status, alcohol abuse, and lifestyle habits have been reported as risk factors (4-7). Immune system disorders, including the imbalanced infiltration of macrophages, Treg cells, and cytokines (8)(9)(10)(11), have also been determined as the underlying causes of CP/CPPS.…”
Section: Introductionmentioning
confidence: 99%